Regulatory Framework of Corporate Governance in Italy and Related Corporate Practices - Gupta, Ambrish (Indian Journal of Research in Capital Markets, 2015)
This paper sought to investigate the regulatory framework of corporate governance in Italy, and gather insights into the related corporate practices in vogue among the listed Italian companies. The paper draws from the Corporate Governance Code published by Comitato per la Corporate Governance (Corporate Governance Committee) ; Regulations for Public Offerings for Subscription and Sales of Financial Products framed by Commissione Nazionale per le SocietÃ e la Borsa (CONSOB), the capital market regulator of Italy ; and the 2013 Report on Corporate Governance of Italian Listed Companies published by CONSOB. It was found that the corporate governance code in Italy is based on the principle of â€œcomply or explainâ€ rather than â€œhave to comply withâ€ norms. The code is thus principle based, and not prescription based. If a company does not comply with any provision of the code, it has to report the reasons for non-compliance. It was also found that though the Italian companies have high ownership concentration, and family controlled management structures, their response to openness and transparency through modern corporate governance mechanisms is improving gradually, though a lot more is desired.